Prognosis of Lymphoma in Patients With Known Inflammatory Bowel Disease: A French Multicentre Cohort Study. (11th March 2020) - Severyns, T; Kirchgesner, J; Lambert, J; Thieblemont, C; Amiot, A; Abitbol, V; Treton, X; Cazals-Hatem, D; Malamut, G; Coppo, P; Galicier, L; Walter-Petrich, A; et al.
Abstract: Background and Aims: The prognosis of lymphoma that occurs in patients with inflammatory bowel disease [IBD] is poorly known. Methods: A multicentre retrospective cohort analysis was done in seven French tertiary centres from 1999 to 2019. Only lymphoma occurring in patients with previous established diagnosis of IBD were analysed. The primary outcome was progression-free survival at 3 years. Results: A total of 52 patients [male 65%, Crohn's disease 79%, median age 48.3 years, median duration of IBD 10.1 years] were included, of whom 37 had been previously exposed to immunosuppressants and/or biologics for at least 3 months and 20 had primary intestinal lymphomas. The lymphoma histological types were: diffuse large B cell lymphomas [ N = 17], Hodgkin lymphomas [ N = 17], indolent B cell lymphomas [ N = 12], and others including T cell lymphomas, mantle cell lymphomas, and unclassifiable B cell lymphoma [ N = 6]. The median follow-up after lymphoma was 5.1 years (interquartile range [IQR] 4–7.8). Progression-free survival at 3 years was 85% in the overall population (95% confidence interval [CI] 75%–96%) with no significant difference between the exposed and unexposed group, 79% for patients exposed to immunosuppressants and/or biologics [95% CI 67%–94%], and 83% for patients diagnosed with primary intestinal lymphoma [95% CI 67%–100%]. No relapse of IBD has been observed during chemotherapy. The IBD relapse rate at the end of the last chemotherapy cycle was 23% at 3 years [95% CI 11%-39%] in the overall population. Conclusions: In this large cohort, the prognosis for lymphomas occurring in IBD appears to be good and similar to what is expected, irrespective of the exposure to biologics and/or immunosuppressants.